Complications after surgery for benign prostatic enlargement: a population-based cohort study in Ontario, Canada - Rano Matta; Erind Dvorani; Christopher Wallis; Amanda Hird; Joseph LaBossiere; Girish Kulkarni; Ronald Kodama; Lesley Carr; Sidney B Radomski; Refik Saskin; Sender Herschorn; Robert K Nam (BMJ Open)
Objectives To examine the complication rates after benign prostatic enlargement (BPE) surgery and the effects of age, comorbidity and preoperative medical therapy.Design A retrospective, population-based cohort study using linked administrative data.Setting Ontario, Canada.Participants 52 162 men≥66 years undergoing first BPE surgery between 1 January 2003 to 31 December 2014.Intervention Medical therapy preoperatively and surgery for BPE.Primary and secondary outcome measures The primary outcome was overall 30-day postoperative complication rates. Secondary outcomes included BPE-specific event rates (bleeding, infection, obstruction, trauma) and non-BPE specific event rates (cardiovascular, pulmonary, thromboembolic and renal). Multivariable analysis examined the association between preoperative medical therapy and postoperative complication rates.Results The 30-day overall complication rate after BPE surgery was 2828 events/10 000 procedures and increased annually over the study period. Receipt of preoperative α-blocker monotherapy (relative rate (RR) 1.05; 95% CI 1.00 to 1.09; p=0.033) and antithrombotic medications (RR 1.27; 95% CI 1.22 to 1.31; p<0.0001) was associated with increased complication rates. Among the ≥80-year-old group, the rate of complications increased by 39% from 2003 to 2014 (RR 1.39; 95% CI 1.21 to 1.61; p<0.0001). The mean duration of medical and conservative management increased by a mean of 2.1 years between 2007 and 2014 (p<0.0001 for trend).Conclusions Thirty-day complication rates after BPE surgery have increased annually between 2003 and 2014. Preoperative medical therapy with alpha blockers or antithrombotics was independently associated with higher rates of complications. Over this time, the duration of conservative therapy also increased.